ANALYSIS OF THE RELATIONSHIP OF TOTAL QUALITY MANAGEMENT IMPLEMENTATION WITH MANAGERIAL PERFORMANCE AT BANK MUAMALAT MEDAN - Henny Zurika Lubis; Bella Aprilia (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study was to analyze the relationship between total quality management (TQM) and managerial performance. The data in this study were obtained from primary data through data collection techniques using a questionnaire method that was distributed by researchers to respondents directly. After collecting the questionnaire, the results of the questionnaire were tested for validity, reliability and hypothesis testing. Based on the results of data analysis, the r square value of 0.721 means that 72.1% of total quality management is related to managerial performance while the remaining 27.9% are other factors that have a relationship between managerial performance and based on simple regression results of 0.812, it shows that any increase in total quality Management (TQM) of 1% will be followed by an increase in managerial performance of 0.812, assuming other variables remain. So it can be concluded that total quality management (TQM) has a positive relationship with managerial performanceKeywords: Total Quality Management (TQM), Managerial Performance